2017
DOI: 10.1093/gbe/evw291
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the intensity of selection on codon bias over time causes contrasting patterns of base composition evolution in Drosophila

Abstract: Four-fold degenerate coding sites form a major component of the genome, and are often used to make inferences about selection and demography, so that understanding their evolution is important. Despite previous efforts, many questions regarding the causes of base composition changes at these sites in Drosophila remain unanswered. To shed further light on this issue, we obtained a new whole-genome polymorphism data set from D. simulans. We analyzed samples from the putatively ancestral range of D. simulans, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
100
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(116 citation statements)
references
References 104 publications
(153 reference statements)
13
100
3
Order By: Relevance
“…This is unexpected, because selection on codon use reduces synonymous site diversity (44), so that a negative relation between Fop and π S would be expected. However, there is little evidence for ongoing selection on codon use at polymorphic synonymous sites in D. melanogaster, in contrast to D. simulans, except for genes with very high codon use bias (45), so that the expected direct effect of selection on codon use on π S in our data is probably negligible. A plausible explanation is that both SSWs and BGS affect π S and Fop in a similar way by reducing the N e for a gene (27,46).…”
Section: Discussioncontrasting
confidence: 65%
“…This is unexpected, because selection on codon use reduces synonymous site diversity (44), so that a negative relation between Fop and π S would be expected. However, there is little evidence for ongoing selection on codon use at polymorphic synonymous sites in D. melanogaster, in contrast to D. simulans, except for genes with very high codon use bias (45), so that the expected direct effect of selection on codon use on π S in our data is probably negligible. A plausible explanation is that both SSWs and BGS affect π S and Fop in a similar way by reducing the N e for a gene (27,46).…”
Section: Discussioncontrasting
confidence: 65%
“…We first discuss the question of how to obtain data on nearly neutral DNA sequence variants. A recent analysis of selection on GC versus AT variants at third codon positions in a Rwandan population of D. melanogaster, using genomewide polymorphism data from the Drosophila Population Genomics Project (Pool et al., ), suggested that only autosomal genes with a high GC content currently experience selection in favour of GC base pairs (Jackson, Campos, Haddrill, Charlesworth, & Zeng, ); there was no statistically significant evidence for such selection on the X chromosome. (Note that the presence of GC vs. AT base pairs at the 3 rd codon position was used as a proxy for preferred versus unpreferred codons, since D. melanogaster preferred codons end in GC (Akashi, ; Zeng, )).…”
Section: Empirical Findingsmentioning
confidence: 99%
“…However, Jackson et al. () found that short intron (SI) sequences, which are thought to evolve nearly neutrally (Clemente & Vogl, ; Parsch, Novozhilov, Saminadin‐Peter, Wong, & Andolfatto, ), showed statistically significant evidence for a departure from neutrality, favouring GC over AT base pairs on the autosomes in both D. simulans and D. melanogaster , and on the X in D. simulans but not D. melanogaster .…”
Section: Empirical Findingsmentioning
confidence: 99%
See 2 more Smart Citations